Skin Grafted Tubularized Incised Urethral Plate for Penile Hypospadias Repair - Mazen O. Kurdi, (Journal of King Abdulaziz University: Medical Sciences, 2023)
Hypospadias is a fairly common congenital defect wherein the urinary tract opening is mispositioned on the ventral aspect of the penis in newborn males. Many techniques have been attempted for the repositioning. Skin grafting of the incised urethral plate was first used in 1998 with encouraging results. This prospective study reports the results of performing this surgical technique at King Abdulaziz University Hospital over the period from January 2010 to December 2014. Thirty patients were enrolled with penile hypospadias, 15 patients had shallow urethral plate, nine patients had small glans and six patients had scarred urethral plate as a result of a previous hypospadias operation. We used continuous suturing (or multiple interrupted stitches) of the proximal end of the skin graft with single stitch fixation of the graft to the depth of the incised urethral plate which helps prevent the separation of the graft by the urinary stream and improve the graft taking. All patients had good caliber of the urethral meatus and the grafted neourethra. Two patients developed urethra-cutaneous fistula without meatal or neourethral stenosis. Grafting of the urethral plate should be considered as an adjunctive method for hypospadias repair especially in patients with small glans, shallow or scarring urethral plate. This grafting resulted in good caliber urethral meatus and neourethra.